2012
DOI: 10.1055/s-0032-1320039
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Brain Stimulation to Treat Aphasia: A Clinical Perspective

Abstract: Transcranial brain stimulation was first introduced and described during mid-1900s. Since that time, the literature on brain stimulation has expanded with spurious advances in techniques and applications, from its use as a purely investigative tool used to better understand brain mechanisms to its use as a clinical treatment for neurologic diseases. This article offers a brief overview of the development, history, and mechanisms of transcranial brain stimulation, as well as an in-depth discussion of transcrani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 84 publications
(263 reference statements)
1
13
0
Order By: Relevance
“…Results showed that 3 weeks of intensive SLT enhanced verbal communication in patients following SRA. Thus, while SLT can lead to improvements, Fridriksson et al [7] also observed that progress is often very slow, especially in the chronic stage.…”
Section: Introductionmentioning
confidence: 99%
“…Results showed that 3 weeks of intensive SLT enhanced verbal communication in patients following SRA. Thus, while SLT can lead to improvements, Fridriksson et al [7] also observed that progress is often very slow, especially in the chronic stage.…”
Section: Introductionmentioning
confidence: 99%
“…The clinical importance of tDCS requires establishing therapy generalization and maintenance of treatment in clinical populations. Two research groups have provided relevant evidence: Fridriksson’s group in spoken naming remediation in post-stroke aphasia 70, 75, 76 and Boggio’s group in associative memory remediation in AD 7779 . After five consecutive stimulations, therapy gains were found to last up to four weeks 62, 75, 77, 80 .…”
Section: Introductionmentioning
confidence: 99%
“…The potential of tDCS for improving performance in naming tasks has been repeatedly demonstrated (e.g. Holland et al, 2011; Monti et al, 2013) and there are already several comprehensive reviews of this literature (Fridriksson, Hubbard, & Hudspeth, 2012; Málly, 2013). In this review, we will instead concentrate on those studies that tested the impact of tES on speech perception or comprehension.…”
Section: Historical Backgroundmentioning
confidence: 97%